Characterization of Al-doped ZnO nanorods grown by chemical bath deposition method - Ahmed, Sabah M. (Innovaciencia, 2018)
Introduction: In recent years a metal oxide semiconductors have been paid attention due to their excellent chemical and physical properties.ZnO (Zinc oxide) is considered as one of the most attractive semiconductor materials for implementation in photo-detectors, gas sensors, photonic crystals, light emitting diodes, photodiodes, and solar cells, due to its novel electrical and optoelectronic properties. There are different uses of metal oxide semiconductors such us, UV photodetectors which are useful in space research’s, missile warning systems, high flame detectors, air quality spotting, gas sensors, and precisely calculated radiation for the treatment of UV-irradiated skin. ZnO is a metal oxide semiconductors and it is used as a transparent conducting oxide thin film because it has the best higher thermal stability, best resistance against the damage of hydrogen plasma processing and relatively cheaper if one compares it with ITO. Materials and Methods: On glass substrates, Al-doped ZnO (AZO) nanorods have been grown by a low -cost chemical bath deposition (CBD) method at low temperature. The seed layer of ZnO was coated on glass substrates. The effect of the Al-doping on the aligned, surface morphology, density, distribution, orientation and structure of ZnO nanorods are investigated. The Al-doping ratios are 0%, 0.2%, 0.8% and 2%. The Aluminum Nitrate Nonahydrate (Al (NO3)3.9H2O) was added to the growth solution, which is used as a source of the aluminum dopant element. The morphology and structure of the Al-doped ZnO nanorods are characterized by field emission scanning electron microscopy (FESEM) and high-resolution X-ray diffractometer (XRD). using the radio RF (Radio frequency) magnetron technique. Results and Discussion: The results show that the Al-doping have remarkable effects on the topography parameters such as diameter, distribution, alignment, density and nanostructure shape of the ZnO nanorods. These topography parameters have proportionally effective with increases of the Al-doping ratio. Also, X-ray diffraction results show that the Al-doping ratio has a good playing role on the nanostructure orientation of the ZnO nanorods. Conclusions: The Aluminum Nitride Nanohydrate considered as a good Aluminu source for doping ZnONR. It is clear from FESEM results that the Al-doping of ZnONR has a remarkable effect on the surface topography of nanorods for all aluminum doping ratios. From XRD patterns, it concludes that as the Al-doping ratio increases, the reorientation of the nanostructure of ZnO increases towards [100] direction. The results obtained also have shown that the average diameter of a nanorod is increased with increasing the ratio of Al-doping.
Keywords: ZnO; Al-Doped; CBD; Nanostructure; Nanorods; Structure